Konsep Pengembangan Bina Prestasi Man Dalam Meningkatkan Mutu Pendidikan - Winarsih, Sri (Literasi: Jurnal Ilmu Pendidikan, 2014)
The Concept of â€œBina Prestasiâ€ fo cused on the Students as the object of education,object of Study.the result of education from the output side,proses and input.The quality of education could be seen from the value that product by education, germ education bath product and..or..that could do by the improvement of the quality education. The program of the improvement of human resources quality. by the improvement of education quality will give the benefit to the.. productivity, moral, work, stabilization, The flexsibility of institution on anticipating environment not only inside but also outside organization.